COMPARISONAL ANALYSIS OF TAX AVOIDANCE PRACTICES BEFORE AND AFTER THE IMPLEMENTATION OF CUTTING CORPORATE INCOME TAX RATES (Empire Study on Manufacturing Companies Listed on Idx For The 2019-2020 Period) - Muhammad Rafli Gindara; Indah Umiyati (Journal of Taxation Analysis and Review, 2023)
This study aims to compare the practice of corporate tax avoidance before and after the implementation of corporate income tax cuts. The research method used is comparative research with a quantitative approach. There are two stages of testing used in this study, namely descriptive statistical analysis to explain the highest value, lowest value, average and standard deviation and the Wilcoxon Signed Rank Test used to compare tax evasion practices before and after tariff changes using the Book Tax Defarance measurement. (BTD). The data used is secondary data obtained from the official website of the Indonesia Stock Exchange. The results showed that there was no difference in tax avoidance practices before and after cutting corporate income tax rates. This is in accordance with the Theory of Planned Behavior in fulfilling tax obligations, each taxpayer will determine the attitude of being a compliant taxpayer or not in accordance with a subjective assessment of the changes in government regulations.